Concepts and methods in modern theoretical chemistry : statistical mechanics - Ghosh, Swapan Kumar; Chattaraj, Pratim Kumar (CRC Press, 2013)
"This volume focuses on the statistical treatment of assemblies of atoms and molecules, including computer simulation methods (both ab initio and classical molecular dynamics) as well as various aspects of chemical dynamics. Other topics covered in the text include nonlinear dynamics, bio-inspired chemistry, condensed matter chemistry, and current research trends in magnetism. Together with Volume I, the text covers all major areas of research in theoretical chemistry, particularly modern trends, and provides both rigorous theoretical foundations as well as applications of vital chemical significance. Contributors are noteworthy experts in the fields and include several Nobel candidates"-- Vydavatelská anotace
Keywords: teoretická chemie; chemická reaktivita; reakční kinetika; kvantová chemie; modelování a simulace; theoretical chemistry; chemical reaktivity; reaction kinetics; quantum chemistry; modeling and simulation; sborníky; papers of several authors